Epileptic seizures induced by pentylenetetrazole kindling accelerate Alzheimer-like neuropathology in 5×FAD mice - Zou, Yulian; Wang, Chengyan; Li, Huang; Zhong, Meihua; Lin, Jin; Hu, Yan; Chen, Zhou; Gan, Chen-Ling (Frontiers in Pharmacology, 2024)
Clinical studies have shown that epileptic seizures worsen Alzheimer’s disease (AD) pathology and related cognitive deficits; however, the underlying mechanism is unclear. To assess the effects of seizures on the progression of AD, chronic temporal lobe epilepsy was induced in five familial AD mutation (5×FAD) mice by kindling with the chemoconvulsant pentylenetetrazole (PTZ) at 3–3.5 months of age. The amyloidogenic pathway, tauopathy, synaptic damage, neuronal death, neurological inflammatory response and associated kinase signaling pathway dysregulation were examined at 9 months of age. We found that APP, p-APP, BACE1, Aβ and kinase-associated p-tau levels were elevated after PTZ kindling in 5×FAD mice. In addition, PTZ kindling exacerbated hippocampal synaptic damage and neuronal cell death, as determined by scanning electron microscopy and terminal deoxynucleotidyl transferase-mediated deoxyuridine triphosphate nick-end labeling (TUNEL) staining, respectively. Finally, the levels of the neuroinflammation markers GFAP and Iba1, as well as the inflammatory cytokine IL-1β, were increased after PTZ insult. PTZ kindling profoundly exacerbated extracellular regulated kinase (ERK)-death-associated protein kinase (DAPK) signaling pathway overactivation, and acute ERK inhibitor treatment downregulated Aβ production and p-APP and p-tau levels in epileptic 5×FAD mice. In addition, long-term use of the antiseizure drug carbamazepine (CBZ) alleviated seizure-induced accelerated amyloid and tau pathology and ERK-DAPK overactivation in 5×FAD mice. Collectively, these results demonstrate that seizure-induced increases in AD-like neuropathology in 5×FAD mice are partially regulated by the ERK-DAPK pathway, suggesting that the ERK-DAPK axis could be a new therapeutic target for the treatment of AD patients with comorbid seizures.